KEEFEKTIFAN KONSUMSI EKSTRAK CURCUMA AERUGINOSA TERHADAP PERUBAHAN LOCHEA PADA IBU POST PARTUM DI BPM AMIRUL MOJOKERTO - KhalimatusSa?diya, Lida; Wahyuningrum, Tria (JURNAL KEPERAWATAN SEHAT, 2016)
Childbed period is a reversion of reproductive organs as before pregnancy. Proces modification lochea need more nutrient essences. The contents of extra curcuma aeureginosa (black temu) is belived can accelerate expulsion of lochea blood. Purpose of this research for analysis the effectiveness consumtion of extract curcuma aeruginosa for changes lochea to postpartum woman. Design used in this research is Quasi-eksperiment with approach method Non-Equivalen control group or non-randomized control group postes design. Population of research are women who bear at BPM Amirul Mojokerto. Technique take a data is consecutive sampling. Sub respondent to each groups are 11 respondent. In this research which to be independent variable is consumtion extract curcuma aeruginosa, scale measuring is nominal. Dependent variable is lochea change to postpartum women, scale measuring is ordinal. Lochea changes quickly in seventh day to be serosa lochea, normal if in seventh day to be sanguilenta lochea, slowly if in seventh day still rubra lochea. Analysis data with dengan crosswise tabulation and Fisher test.The result of crosswise tabulation research be obtained in control group more than a half of respondent get treatment lochea with normal that are 7 people (64%). In experiment group more than a half of respondent get treatment with normal that are 6 people (55%). The change of lochea with quickly more happen in experiment group that are 5 people (45%) compared in control group. The result of statistic if there is not effect after cosumtion extract curcuma aeruginosa to lochea change in postpartum women (p=0.125).Conclusion There is no effect after consumtion extract curcuma aeruginosa to lochea change for postpartum mother.Key word : curcuma aeruginosa, Lochea, postpartum